Pengaruh Struktur Kepemilikan, Leverage dan Return On Asset (ROA) Terhadap Kebijakan Dividen pada Perusahaan Manufaktur Yang Terdaftar Dibursa Efek Indonesia Tahun 2021-2023 - I Gede Surya Suwana Saputra; Emilia Gustini (Moneter : Jurnal Ekonomi dan Keuangan, 2024)
This research aims to analyze the influence of liquidity, ownership structure, leverage, and Return On Assets (ROA) on dividend policy in companies on the Indonesia Stock Exchange (BEI) for the 2021-2023 period. Dividend policy is an important decision for a company in determining the allocation of profits that will be distributed to shareholders and those that will be retained for investment purposes. Liquidity reflects a company's ability to meet short-term obligations, while ownership structure highlights the role of shareholders and managers in decision making. Leverage, which indicates the use of debt in financing, and ROA, as an indicator of profitability, are also considered important factors influencing dividend policy. This research differs from previous research with the addition of leverage variables as well as differences in population, sample and research period. It is hoped that the results of this research will provide a more comprehensive understanding of the factors that influence dividend policy and its implications for company value.